2014
DOI: 10.1111/sjop.12123
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in working memory as a function of APOE genotype in midlife and old age

Abstract: Previous investigations into whether the APOE-ε4 allele exerts cognitive effects at midlife have been inconclusive. We have advanced a “cognitive phenotype” hypothesis arguing that the ε4 allele of the apolipoprotein E gene (APOE) is associated with lower efficiency of neuronal plasticity thereby resulting in poorer cognitive performance independently of the pathology of Alzheimer’s disease (Greenwood et al., 2005). This hypothesis is best tested at midlife, prior to the neuron loss associated with AD diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 75 publications
6
29
0
Order By: Relevance
“…A potential factor increasing the risk of the development of cognitive impairment with age is apolipoprotein E (APOE) ε4 carrier status [3, 4]. The human APOE gene is a polymorphic protein, consisting of three alleles (ε2, ε3 and ε4) that code for three protein isoforms, known as APOE2, APOE3, and APOE4.…”
Section: Introductionmentioning
confidence: 99%
“…A potential factor increasing the risk of the development of cognitive impairment with age is apolipoprotein E (APOE) ε4 carrier status [3, 4]. The human APOE gene is a polymorphic protein, consisting of three alleles (ε2, ε3 and ε4) that code for three protein isoforms, known as APOE2, APOE3, and APOE4.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal measures (Greenwood et al, 2014) revealed no genotype difference across trials with relatively low WM demand. On trials incorporating a mismatch between encoded and target stimuli, and hence placing greater demand on WM resources, however, performance of ε4+ improved over 3 years, whilst performance of the ε4-group remained stable.…”
Section: Longitudinal Assessmentsmentioning
confidence: 99%
“…Several studies suggest that ε4+ show significantly greater memory decline from mid-adulthood (Caselli et al, 2009;Kozauer, Mielke, Chan, Rebok, & Lyketsos, 2008), with this effect isolated to delayed memory in two studies (Greenwood, Sunderland, Putnam, Levy, & Parasuraman, 2005b;Greenwood et al, 2014). Performance change across an average of 3.8 years was investigated for measures of memory (Jochemsen, Muller, van der Graaf, & Geerlings, 2012), with participants stratified by age.…”
Section: Longitudinal Assessmentsmentioning
confidence: 99%
“…The current report summarizes my results using both cross-sectional and longitudinal approaches, with a particular emphasis on middle-aged adults between the ages of 40 and 60 years. The focus on middle-aged adults will serve to establish whether any observed changes in listening comprehension parallel the well-documented declines in both sensory and cognitive abilities in this age group (Greenwood, Espeseth, Lin, Reinvang, & Parasuraman, 2014;Morrell, Gordon-Salant, Pearson, Brant, & Fozard, 1996).…”
mentioning
confidence: 99%
“…On one hand, the expectation might be systematic and progressive declines in listening comprehension across the adult lifespan that parallel age-related declines in auditory thresholds (Morrell et al, 1996) and cognitive abilities (Greenwood et al, 2014). For example, Schneider, Daneman, Murphy, and See (2000) found that when audibility was equated across groups of younger and older adults, they performed similarly on measures of listening comprehension.…”
mentioning
confidence: 99%